Involvement of TRP Channels in Adipocyte Thermogenesis: An Update - Sun, Wuping; Luo, Yixuan; Zhang, Fei; Tang, Shuo; Zhu, Tao (Frontiers in Cell and Developmental Biology, 2021)
Obesity prevalence became a severe global health problem and it is caused by an imbalance between energy intake and expenditure. Brown adipose tissue is a major site of mammalian non-shivering thermogenesis or energy dissipation. Thus, modulation of BAT thermogenesis might be a promising application for body weight control and obesity prevention. TRP channels are non-selective calcium-permeable cation channels mainly located on the plasma membrane. As a research focus, TRP channels have been reported to be involved in the thermogenesis of adipose tissue, energy metabolism and body weight regulation. In this review, we will summarize and update the recent progress of the pathological/physiological involvement of TRP channels in adipocyte thermogenesis. Moreover, we will discuss the potential of TRP channels as future therapeutic targets for preventing and combating human obesity and related-metabolic disorders.